Dynamics of Base Erosion and Profit Shifting (BEPS) Tax Planning Strategy in the Global Sustainable Development Framework - Wahyu, Fitri Pebriani; Putri, Shabrina Magistra (Jurnal Perpajakan dan Keuangan Publik, 2025)
Tax as the main source of income for the state has an important role in financing sustainable development. However, the dynamics of tax planning are increasingly complex with the issue of Base Erosion and Profit Shifting (BEPS), which has become a major concern for G20 member countries since 2014. BEPS, which refers to the practice of tax avoidance by multinational companies through shifting profits to countries with low tax rates, has created global economic injustice and hampered development. This article discusses the implementation of the BEPS strategy in the context of sustainable development, highlighting Indonesia's role in adopting this policy in its taxation system. BEPS, introduced by the OECD, aims to improve the international tax framework to suit the dynamics of the global economy, reduce tax avoidance, and ensure fair contributions from companies, communities, and countries. This strategy also supports economic stability and creates a healthy business environment, stimulates domestic investment, and contributes to the achievement of sustainable development goals (SDGs). The implementation of BEPS in Indonesia, especially in the digital economy aspect, reflects the country's commitment to strengthening fiscal resilience and supporting inclusive and sustainable development. In conclusion, the implementation of BEPS plays a crucial role in creating a transparent, fair and sustainable tax system, which can support inclusive economic growth and reduce social inequality.